Eco-Literacy Content in Language Learning and its Impact on Students’ Pro-Environmental Habit at State Junior High School (SMPN) 4 of Ternate City - Ali, Silvani Umar; Lestari, Sri Ayu Budi; Bahara, Susana R; Jusnita, Naniek; Yusup Supriyono, Yusup Supriyono; Putri, Ismi Oktalia (English Education and Literature Journal (E-Jou), 2024)
One of the efforts to develop ecological literacy skills can be done through formal education. The system owned by formal education, namely schools, is able to induce components that support ecological literacy skills, including knowledge, skills, attitudes and actions. The purpose of this study was to find out what eco-literacy content is in language learning and its impacts on students' pro-environmental habit. This research was conducted at SMP Negeri 4 Kota Ternate. The method used in this research is content analysis on textbooks and students interview to obtain information and practical experience of students. Based on the results of data analysis, in class VII and IX, there is one unit each in the textbook which contains literacy ecology with the respective themes 'Let's Clean Up' and 'Let's Live Healthy' (Let’s live a healthy life). For the first theme, the significant impact that is visible and integrated in daily activities at school is that students always maintain cleanliness by sweeping and cleaning before starting lessons, throwing garbage in its place, always cleaning the black-board after use, wearing clean and tidy uniforms when going to school. Interview data also showed that students always helped their parents to clean the house on Sundays, cut thick branches, clean gutters, clean bedrooms, etc. The second theme is about maintaining a healthy life, there are some students who bring food from home because it is cleaner and safer, students regularly cut their nails, cut their hair (for boys), bathe with soap, brush their teeth and wear perfume to school. Based on the analysis and interview data above, it can be concluded that students know, understand, and practice the habit of maintaining cleanliness and healthy living practices in daily life at school and at home, meaning that eco-literacy learning has a positive impact on students' understanding of environmental insights both at school and at home.